Formare le competenze relazionali e comunicative per promuovere l’accoglienza delle famiglie dei bambini con bisogni educativi speciali nei servizi educativi per la prima infanzia - Pennazio, Valentina; Bochicchio, Franco (Rivista Italiana di Educazione Familiare, 2020)
Starting from the results of a research conducted in Liguria with families of children with disabilities and with nursery educators, the contribution intends to reflect on the importance of developing good interpersonal and communicative skills in educators of early childhood services. The results of the research in fact highlight how the choice of families to allow their child with disabilities to attend the nursery depends, rather than on specific knowledge on disability, on the ways in which educators know how to welcome parents, support them and involve them in the realization of the educational experience. The importance of developing soft skills raises some questions around which we try to reason in the contribution. In particular, we want to understand if the current university courses manage to encourage the development of these skills and which teaching methodologies should be incentivized to achieve this goal.